2019
DOI: 10.1101/655332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TNAP limits TGF-β-dependent cardiac and skeletal muscle fibrosis by inactivating SMAD2/3 transcription factors

Abstract: 2Fibrosis is associated with almost all forms of chronic cardiac and skeletal muscle diseases. The accumulation of extracellular matrix impairs the contractility of muscle cells contributing to organ failure. Transforming growth factor beta (TGF-β) plays a pivotal role in fibrosis, activating pro-fibrotic gene programs via phosphorylation of SMAD2/3 transcription factors. However, the mechanisms that control dephosphorylation of SMAD2/3 have remained poorly characterized. Here we show that tissue non-specific … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In addition, lnc‐H19 knockdown inhibited the activation of TGFβ/Smad pathway to regulate myoblast fibrogenesis. It was reported that TGFβ/Smad pathway is critical in skeletal muscle fibrosis 9,22,32,33 . Previous studies verified that knockdown of lnc‐H19 suppressed the activation of TGFβ/Smad pathway 13,34 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, lnc‐H19 knockdown inhibited the activation of TGFβ/Smad pathway to regulate myoblast fibrogenesis. It was reported that TGFβ/Smad pathway is critical in skeletal muscle fibrosis 9,22,32,33 . Previous studies verified that knockdown of lnc‐H19 suppressed the activation of TGFβ/Smad pathway 13,34 .…”
Section: Discussionmentioning
confidence: 91%
“…It was reported that TGFβ/Smad pathway is critical in skeletal muscle fibrosis. 9,22,32,33 Previous studies verified that knockdown of lnc-H19 suppressed the activation of TGFβ/Smad pathway. 13,34 Consistently, our study showed that when lnc-H19 was knockdown in vitro, expression levels of TGFβ/Smad pathway proteins decreased (Figure 2E).…”
Section: Discussionmentioning
confidence: 94%
“…They also could interfere with the normal process of muscle regeneration and a loss of muscle function 31,32 . Recent studies have implicated an increase in expression of TGFβ and cellular communication network factor 2 (also known as connective tissue growth factor) following muscle injury as a potential contributing factor in postdenervation muscle fibrosis, 33,34 and preliminary investigations into limiting fibrosis via modulation of these pathways show promise 35‐37 . Fibroadipogenic progenitors have also been demonstrated to increase in number following denervation and secrete elevated levels of IL‐6, promoting muscle atrophy and fibrosis 38 …”
Section: Discussionmentioning
confidence: 99%
“…Due to the wide and variable expression of TNAP in various cell types, TNAP-expressing cells can also be targeted using the Cre-Lox system. For example, using mice with tamoxifen-inducible inactivation of transforming growth factor β (TGF-β) in TNAP-expressing cells ( Tnap cre ; Tgfßr2 fl/fl ), researchers have shown that TNAP mitigates TGF-ß-dependent cardiac and skeletal muscle fibrosis through inactivation of SMAD2/3 transcription factors [ 89 ].…”
Section: Models and Tools To Study Tnapmentioning
confidence: 99%